Development, testing and reporting of mobile apps for psycho-social interventions: lessons from the pharmaceuticals - Naeem, Farooq; Syed, Yumeen; Xiang, Shuo; Shokraneh, Farhad; Munshi, Tariq; Yang, Mega; Adams, Clive E.; Farooq, Saeed (Omics Publishing Group, 2015)
The mobile Health offers great potential for delivery of Psycho-social Interventions. So far, the researchers have focused mainly on efficacy, and to some extent feasibility of Psycho-social Interventions. Poor reporting of development and initial testing has been highlighted in the recent published literature. This is not surprising considering the lack of guidance from the national regulatory agencies in developed countries. A lack of standard ways of development and testing of apps makes scientific evaluation of the intervention and replicability almost impossible. Replicabiliy is an essential component of good science. We are proposing a pathway to develop, test and report new mobile apps that deliver Psycho-social Intervention, that is based on current practices of approval of new drugs by the US, Food and Drug Administration (FDA). This proposed process consists of modifications in the current app development process, i.e., planning, alpha and beta testing. We are also suggesting an additional delta stage of testing. We note the advantages and limitations in using such approach.